2012
DOI: 10.1016/j.media.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for improved tractography and quantitative analysis of probabilistic fibre tracking curves

Abstract: This paper presents a novel approach for improved diffusion tensor fibre tractography, aiming to tackle a number of the limitations of current fibre tracking algorithms, and describes a quantitative analysis tool for probabilistic tracking algorithms. We consider the sampled random paths generated by a probabilistic tractography algorithm from a seed point as a set of curves, and develop a statistical framework for analysing the curve-set geometrically that finds the average curve and dispersion measures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The tracking procedure used in deterministic tractography terminates when it reaches regions with fibre crossings, 38 and this tends to reduce sensitivity. Probabilistic tractography overcomes this shortcoming, and offers a natural approach to modelling uncertainty by generating multiple curves originating from a seed point, 39 providing a more comprehensive picture of connectivity. The probabilistic algorithm has better test-retest reliability and is more robust than deterministic tractography in areas of high uncertainty (notably fibre crossings).…”
Section: J Psychiatry Neurosci 2018;43(6)mentioning
confidence: 99%
“…The tracking procedure used in deterministic tractography terminates when it reaches regions with fibre crossings, 38 and this tends to reduce sensitivity. Probabilistic tractography overcomes this shortcoming, and offers a natural approach to modelling uncertainty by generating multiple curves originating from a seed point, 39 providing a more comprehensive picture of connectivity. The probabilistic algorithm has better test-retest reliability and is more robust than deterministic tractography in areas of high uncertainty (notably fibre crossings).…”
Section: J Psychiatry Neurosci 2018;43(6)mentioning
confidence: 99%
“…In patients 2, 3, and 5, an occipital, transtentorial approach through the quadrigeminal cistern may have been a good alternative as proposed by surgeon 1 ( Table 2). The technical limitations of probabilistic tractography also apply to our study 37,54,55 (eg, resolution of DTI, crossing fibers, thresholding, manual delineation of masks, false-positive connectivity within the tumor). Thalamic segmentation cannot determine the border of thalamic structures in complete consistency with the anatomy, but inaccuracy may not be greater than a few millimeters.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of structural networks based on DTI, most previous structural networks were constructed using deterministic fibre tracking algorithms (Shu et al, 2018;Yan et al, 2018). In comparison, the probabilistic fibre tracking algorithm of this study considered the uncertainty of fibre direction estimation, thereby improving the accuracy of white matter fibre tracking (Ratnarajah et al, 2012). Regarding the distribution of hubs and consensus connections of structural network, our results indicated that the discriminative features of structural network based on DTI and the morphological network based on sMRI involved in overlapped and multiple cortical-subcortical brain regions, such as the frontal lobe, PhG, Tha, and BG.…”
Section: Alterations In Structural Brain Networkmentioning
confidence: 99%